2019
DOI: 10.1007/s12122-019-09291-2
|View full text |Cite
|
Sign up to set email alerts
|

Wage Returns to English Proficiency in Poland

Abstract: We investigate the effect of English language proficiency on the wages of native full-time employees in Poland. Using a unique data set with information on over 600,000 survey respondents polled over the five-year period from 2013 to 2017, we employ an IVapproach founded on a natural experiment -namely, the reform of foreign language instruction in Polish schools. Our preferred estimates indicate that monthly wages for those individuals with 'good' or 'very good' knowledge of English exceeded the wages of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, advanced German or French proficiency corresponded with similar wage increases, which suggests that employers value multilingualism rather than proficiency in English per se. Another study also found that the financial benefits of knowing foreign languages varied somewhat by gender: Proficiency in English corresponded with a 60% increase in monthly wages for men but a 50% increase for women, which was a statistically significant difference (Adamchik et al., 2019).…”
Section: English In Contemporary Polish Societymentioning
confidence: 98%
“…Interestingly, advanced German or French proficiency corresponded with similar wage increases, which suggests that employers value multilingualism rather than proficiency in English per se. Another study also found that the financial benefits of knowing foreign languages varied somewhat by gender: Proficiency in English corresponded with a 60% increase in monthly wages for men but a 50% increase for women, which was a statistically significant difference (Adamchik et al., 2019).…”
Section: English In Contemporary Polish Societymentioning
confidence: 98%